2009
DOI: 10.1063/1.3193681
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic line motion and stochastic flux conservation for nonideal hydromagnetic models

Abstract: We prove that smooth solutions of non-ideal (viscous and resistive) incompressible magnetohydrodynamic equations satisfy a stochastic law of flux conservation. This property involves an ensemble of surfaces obtained from a given, fixed surface by advecting it backward in time under the plasma velocity perturbed with a random white-noise. It is shown that the magnetic flux through the fixed surface is equal to the average of the magnetic fluxes through the ensemble of surfaces at earlier times. This result is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 50 publications
(110 reference statements)
3
41
0
Order By: Relevance
“…Contrary to the traditional arguments of Taylor & Green (1937), vortex-lines in the ideal limit will not be "frozen-into" the turbulent fluid flow in the usual sense. Similar results holds also for magnetic field-line motion in resistive magnetohydrodynamics (Eyink 2009), and spontaneous stochasticity then implies the possibility of fast magnetic reconnection in astrophysical plasmas for arbitrarily small electrical conductivity (Eyink et al 2013). In our companion papers II, III we extend the derivation of our Lagrangian FDR to wall-bounded flows, and derive similar relations between anomalous scalar dissipation and spontaneous stochasticity, as well as new Lagrangian relations for Nusselt-Rayleigh scaling in turbulent convection.…”
Section: Summary and Discussionsupporting
confidence: 65%
“…Contrary to the traditional arguments of Taylor & Green (1937), vortex-lines in the ideal limit will not be "frozen-into" the turbulent fluid flow in the usual sense. Similar results holds also for magnetic field-line motion in resistive magnetohydrodynamics (Eyink 2009), and spontaneous stochasticity then implies the possibility of fast magnetic reconnection in astrophysical plasmas for arbitrarily small electrical conductivity (Eyink et al 2013). In our companion papers II, III we extend the derivation of our Lagrangian FDR to wall-bounded flows, and derive similar relations between anomalous scalar dissipation and spontaneous stochasticity, as well as new Lagrangian relations for Nusselt-Rayleigh scaling in turbulent convection.…”
Section: Summary and Discussionsupporting
confidence: 65%
“…An historical account of the main results obtained between those two works may be found there. Lately, similar results have been derived in the incompressible amplified, magnetohydrodynamic, frame by Eyink [10]. In particular, he showed that viscous and resistive incompressible magnetohydrodynamic (MHD) equations were equivalent to having some stochastic conservation laws, and that similar results could be obtained in more refined non-ideal models, such as the Hall MHD and two-fluid plasma models with incompressible velocities.…”
Section: Non-ideal Effects and Stochasticitysupporting
confidence: 57%
“…This formulation has been since extended to domains with solid boundary [13] and to a Riemannian manifold when the de Rham-Hodge Laplacian is the viscous dissipation operator [14]. Finally, Eyink [15] extended the work of Constantin and Iyer to nonideal hydromagnetic models. There, a stochastic analogue of the classical Alfvén theorem was proved to be equivalent to smooth solutions of the deterministic, nonideal, incompressible magnetohydrodynamic equations.…”
Section: Resultsmentioning
confidence: 99%